Surgical Outcome of Anorectal Malformations of Neonates in Dhaka Medical College Hospital (KYAMC Journal, 2025)
Background: ‘Imperforate anus’ has been a well-known condition since antiquity. Nowadays, it is broadly termed as anorectal malformations (ARMs). Objective: To determine the incidence, initial management and surgical outcome in children with ARMs. Materials and Methods: This prospective descriptive study included neonates admitted with ARMs in Dhaka Medical College Hospital during 24 24-month period (January 2015 – December 2016). A total of 118 neonates were admitted (23.6 % of the total neonatal surgical admission) during this period. Results: The majority of the ARMs neonates were presented at the first week of life 109 (92.37%). Gender distribution of neonates: males were 80, females were 38, ratio (m: f) was 2.11: 1, age at presentation of neonates ranged from 0.04 day (1 hour) to 28 days (mean 3.27 days), presenting weight of neonates ranging from 1.5 - 5 in kilograms (mean 2.67 kg). The majority of patients were a high variety of ARMs 80 (67.79%), low variety of ARMs 27 (22.88%) and cloaca 11 (09.32%). Most of the surgical procedures were pelvic colostomy 80 (21.1%) followed by anoplasty 27 (7.0%), and transverse colostomy 11(9.32%). 16 neonates died, so mortality was 13.56%. Mortality was higher in low-birth-weight babies: 68.75%. Premature/preterm (short gestational age) delivery 56.25%. 14 (17.5%) after pelvic colostomy and 2 (18.18%) died after transverse colostomy.Conclusion: An effective healthcare system, proper training for medical professionals and meticulous perineal examination of all neonates at birth are key requirements of early detection of ARMs. Early presentation of surgical neonates ensures better surgical outcomes.